2015
DOI: 10.3171/2014.10.jns14759
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced anticancer properties of lomustine in conjunction with docosahexaenoic acid in glioblastoma cell lines

Abstract: abbreviatioNs BCA = bicinchoninic acid; CSC = Cell Systems Corporation; DHA = docosahexaenoic acid; DMEM = Dulbecco's modified essential medium; DPA = docosapentaenoic acid; ED 50 = median effective dose; EMEM = Eagle's minimum essential medium; EPA = eicosapentaenoic acid; FBS = fetal bovine serum; HBMEC = human brain microvascular endothelial cell; HCCMEC = human cerebral cortex microvascular endothelial cell; OD = optical density; PARP = poly (ADP-ribose) polymerase; PBS = phosphate-buffered saline; PUFA = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…In a recent experimental study, Harvey et al assessed the anticancer properties of CCNU in glioblastoma cell lines, and found that the combination of docosahexaenoic acid (DHA) and CCNU strongly induced Uppsala 87 malignant glioma (U87-MG0 apoptosis and necrosis as indicated by flow cytometric analysis. 35 They suggested a potential role for a…”
Section: Discussionmentioning
confidence: 99%
“…In a recent experimental study, Harvey et al assessed the anticancer properties of CCNU in glioblastoma cell lines, and found that the combination of docosahexaenoic acid (DHA) and CCNU strongly induced Uppsala 87 malignant glioma (U87-MG0 apoptosis and necrosis as indicated by flow cytometric analysis. 35 They suggested a potential role for a…”
Section: Discussionmentioning
confidence: 99%
“…These lipids, such as the fatty acid docosahexaenoic acid, have been observed to demonstrate potent anticancer properties against a variety of cancer types such as breast cancer, ovarian cancer, glioblastomas, etc. [ 211 , 212 , 213 , 214 ]. The nanocapsules, comprising shells of bioactive lipids, are able to deliver drugs and other biologically sensitive molecules to specific cells or organs, thus enhancing the potency and cancer therapeutic potential [ 211 , 215 ].…”
Section: Challenges For Phytochemicals In Cancer Therapy and Emergmentioning
confidence: 99%
“…Such synergistic behavior of DHA with arsenic acid in number of cell lines (Baumgartner et al, 2004) and with paclitaxel in BT-474 and SK-BR-3 breast cell lines that have been linked to lipid peroxidation (Menendez et al, 2005) is reported. DHA-mediated enhanced uptake of CUR by modulating plasma membranes in glioblastomas could have also played a critical role (Harvey et al, 2015). Studies have shown that DHA incorporation changed the chemical and physical properties of cell membrane phospholipids to enhance uptake of various anticancer drugs, including vincristine in a drug-resistant neuroblastoma cell line (Ikushima et al, 1990).…”
Section: Subacute Toxicity and Nasal Toxicitymentioning
confidence: 99%